2019
DOI: 10.3389/fmicb.2019.02294
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics and Biochemistry of Cell Wall Structure and Synthesis in Neurospora crassa, a Model Filamentous Fungus

Abstract: This review discusses the wealth of information available for the N. crassa cell wall. The basic organization and structure of the cell wall is presented and how the wall changes during the N. crassa life cycle is discussed. Over forty cell wall glycoproteins have been identified by proteomic analyses. Genetic and biochemical studies have identified many of the key enzymes needed for cell wall biogenesis, and the roles these enzymes play in cell wall biogenesis are discussed. The review includes a discussion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 134 publications
0
50
0
Order By: Relevance
“…Chitosan application to plants fits into the delicate relationship between the host and pathogenic fungi and involves the primary cell‐wall defense mechanisms. A link between pathogenicity and the enzymes that synthesize the fungal cell wall has been demonstrated in numerous studies (Arana et al., 2009; Geoghegan et al., 2017; Lenardon, Munro, & Gow, 2010; Levdansky, Kashi, Sharon, Shadkchan, & Osherov, 2010; Oliveira‐Garcia, & Deising, 2013; Patel & Free, 2019), and depolymerization of the cell walls of plant pathogenic fungi following the infection, evading plant immune recognition, has been reported (Geoghegan et al., 2017). It has been reported that the strategy of some fungal pathogens to evade plant immunity is to convert chitin into chitosan (Lopez‐Moya et al., 2019).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Chitosan application to plants fits into the delicate relationship between the host and pathogenic fungi and involves the primary cell‐wall defense mechanisms. A link between pathogenicity and the enzymes that synthesize the fungal cell wall has been demonstrated in numerous studies (Arana et al., 2009; Geoghegan et al., 2017; Lenardon, Munro, & Gow, 2010; Levdansky, Kashi, Sharon, Shadkchan, & Osherov, 2010; Oliveira‐Garcia, & Deising, 2013; Patel & Free, 2019), and depolymerization of the cell walls of plant pathogenic fungi following the infection, evading plant immune recognition, has been reported (Geoghegan et al., 2017). It has been reported that the strategy of some fungal pathogens to evade plant immunity is to convert chitin into chitosan (Lopez‐Moya et al., 2019).…”
Section: Discussionmentioning
confidence: 92%
“…There are direct links between the cell wall and cell membranes, as the synthesis of key cell‐wall components (e.g., glucans, chitin) occurs at the plasma membrane, with the associated synthase enzyme complexes (Maddi, & Free, 2010). The chitin is localized in the membrane proximal portion of the cell wall and is incorporated into the wall matrix by being cross‐linked to the glucans (Patel & Free, 2019). Previous studies have investigated the role of plasma membrane in the sensitivity of fungi to chitosan showing that the plasma membrane of chitosan‐sensitive fungi is more fluid and richer in polyunsaturated free fatty acids than in chitosan‐resistant fungi (Palma‐Guerrero et al., 2009, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A closer related species to T. harzianum and a Sodariomycete, N. crassa , revealed a BLAST-based orthologue NCU04431 to gluc31 (96% query coverage, 56.74% identity), also encoding a GH16 member. A knockout of NCU04431 was recently shown to exhibit a wild type growth morphology ( Patel and Free, 2019 ), which may suggest that gluc31 only plays a specific role in cell wall biogenesis of T. harzianum . Taken together with transcriptional data from A. niger , we do not expect that other non-Crh GH16 enzymes of A. niger act in chitin to glucan transglycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Neurospora crassa and Aspergillus fumigatus both encode five orthologues, whereas A. niger contains seven orthologues ( Pel et al, 2007 ). All these three fungi displayed wild type growth morphology for all single knockouts strains ( Fang et al, 2019 , Patel and Free, 2019 , van Leeuwe et al, 2019 ). In case of A. fumigatus, Af Crh5p was structurally and functionally characterized as a true transglycosylase with both homo- and heterotransglycosylation activity, additionally identifying both donor and acceptor substrate binding kinetics and moieties ( Fang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 97%
“…Chitin and β-glucan are the primary polysaccharides involved in cell wall integrity in most fungi [ 9 , 43 ]. There are dynamic levels of chitin and β-glucan biosynthesis during hyphal tip extension [ 44 , 45 ]. In conidia, the VosA-VelB complex negatively regulates the expression of various genes, including cell wall-related genes, resulting in the repression of chitin and β-glucan biosynthesis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%